Cold War atmosphere: Distorted information and facts in the case of Free Europe balloons. (24th April 2020) - Georgiev, Georgi
Abstract: Radio Free Europe used balloons to drop leaflets in an attempt to supplement radio with printed words in the 1950s—a historical moment when closing borders, censoring the press, jamming foreign radios, tapping telephone lines, and tracking letters from abroad created an almost hermetically sealed space without many means for exchanging information across the Iron Curtain. This article traces how distorted and limited information shaped Cold War propaganda and practices of information‐gathering. The article further examines unpredictable environmental factors that were transformed into persuasive political rhetoric. A comparative analysis of communist media shows similarities of imagination in a visual propaganda campaign across five communist countries. Fantasies evolved into an object of public interest when propaganda strategies embraced a language of facts.